Odpowiedzi

2009-11-27T15:52:51+01:00
A) x²-(x-2)²=16
x²-x²+4x-4=16
4x-4=16
4x=20 / :4
x=5

b) x(x-1)=(x+1)²+2
x²-x= x²+2x+1+2
x²-x-x²-2x=3
-3x=3 / : (-3)
x=-1

c) (x-3)²=(x-1)(x+2)-3
x²-6x+9=x²+2x-x-2+3
x²-6x-x²+2x-x=-2+3-9
-5x=-8 / :(-5)
x= 8/5
x=1 3/5= 1,6


Najlepsza Odpowiedź!
2009-11-27T15:53:31+01:00
A) x2-(x-2)do kwadratu=16
x2-(x2-4x+4)=16
x2-x2+4x-4=16
4x=20
x=5
b)x(x-1)=(x+1)do kwadratu+2
x2-x=x2+2x+1+2
x=x2+2x+3
x-x2-2x=3
-x-2x=3
-3x=3
x=-1
c)(x-3)do kwadratu=(x-1)(x+2)-3
x2-6x+9=x2+2x-x-2-3
x2-x2-6x-x=-5-9
-7x=-14
x=2
2009-11-27T15:55:51+01:00
A) ײ-(×-2)²=16
x² - x² - 4 = 16
-4 = 16 /: -4
0 ≠ -4


b) ×(×-1)=(×+1)²+2
x² - x = x² + 1 + 2 / - x²
-x = 3 / : -1
x = -3


c) (×-3)²=(×-1)(×+2)-3
x² - 9 = x² + 2x - x - 2 - 3
x² - 9 = x² + x -5 / -x² / +5
-4 = x
x = -4